European Union debt financing: Leeway and barriers from a legal perspective - Sebastian Grund; Armin Steinbach (Bruegel, 2023)
We explore legal leeway for two approaches to debt-financing European Union spending: creation of extra-budgetary, one-off and temporary EU funds to finance European public goods (similarly to NextGenerationEU), and debt-financing the EU's regular budget, hence creating an on-budget, permanent borrowing capacity at EU level. We find that NGEU could in principle be replicated. This would require an amendment to the Own Resources Decision (ORD) - a unanimous Council decision that designates the main sources of EU financing and requires ratification by each member state - to authorise borrowing and specify how the borrowing proceeds are to be used. However, this approach would be constrained by the legal requirement that financing EU spending through 'other revenues' (as opposed to 'own resources' designated as such in the ORD) remain exceptional. As a result, no permanent EU tasks could be financed through NGEU-like funds and NGEU-like financing could not exceed financing through 'own resources'. We also find that, while EU primary law does not stop the EU from debt-financing its budget, the scope for EU borrowing would remain severely limited compared to a sovereign state. The permissible amount of borrowing must be specified in the ORD and the EU must be able to meet its debt service in any year, which must be secured by a sufficient amount of (non-borrowed) own resources. Finally, considerable flexibility exists for the spending of borrowed funds, regardless of whether this occurs through new NGEU-like extrabudgetary funds or on budget. Borrowed funds could be allocated to climate funding, cohesion policy, infrastructure or research. In the event that borrowing proceeds are established as an 'own resource' in an appropriately amended ORD, borrowed funds could even be used for general financing of the EU budget.
Keywords: 330; public debt; financial regulation; european commission